Host immune responses in aged rhesus macaques against BBV152, an inactivated SARS-CoV-2 vaccine, and cross-neutralization with beta and delta variants - Patil, Dilip R.; Shete, Anita M.; Yadav, Pragya D.; Sapkal, Gajanan N.; Deshpande, Gururaj R.; Kaushal, Himanshu; Mohandas, Sreelekshmy; Fulari, Siddharam; Jain, Rajlaxmi; Kumar, Ajay; Abraham, Priya (Frontiers in Immunology, 2023)
Magnitude and duration of immune response to Covid-19 vaccination in elderly is known to be advesrsely affected due to immunoscenecence and inflammaging. The threat of emerging variants warrents studies on immune response in elderly to primary vaccination and booster doses so as to understand the effectiveness of vaccines in countering the threat of emerging variants. Nonhuman primates (NHPs) are ideal translational models, as the immunological responses in NHPs is similar to human, so it enables us to understand host immune responses to the vaccine. we initially studied humoral immune responses in aged rhesus macaques employing a three-dose regimen of BBV152, an inactivated SARS-CoV-2 vaccine. Initially, the study investigated whether the third dose enhances the Nab titer against the homologous virus strain (B.1) and important VOCs (Beta and Delta) in aged rhesus macaques immunized with BBV152, adjuvanted with algel/algel-IMDG(Imidazoquinoline). Later, we also attempted to understand cellular immunity in terms of lymphoproliferation against γ-inactivated SARS-CoV-2 B.1 and delta in naïve and vaccinated rhesus macaques after a year of the third dose. Following the three-dose regimen with 6 ug of BBV152 with algel-IMDG, animals had increased Nab responses across all SARS-CoV-2 variants, which suggested the importance of booster dose for the enhanced immune response against SARS-CoV-2 circulating variants. The study also revealed the pronounced cellular immunity against B.1 and delta variants of SARS-CoV-2 in the aged rhesus even after a year of vaccination.